Students and instant messaging: a survey of current use and demands for higher education - Gijs de Bakker; Peter Sloep; Wim Jochems (Association for Learning Technology, 2007)
Instant messaging (IM) is the term used to describe the technology through which ‘users can set up a list of partners who will be able to receive notes that pop up on their screens the moment one of them writes and hits the send button'. While early use could be described as mainly for fun, IM today is a serious communication medium. Remarkably, it seems that educational institutions have been doing very little with it, while several studies indicate that it could indeed be a valuable tool in education. As a first step towards a better understanding of the educational use of IM, we want to gain insights in how students currently use IM and what opportunities they themselves see for the medium. To that end we conducted a survey among students of the Fontys University of Applied Sciences in The Netherlands. A large majority of the participating students indicated using IM for their studies. Also, when asked about their demands for a possible educational implementation, the majority were positive